Unicast position-based routing protocols for ad-hoc networks - Kiah, M.L.M.; Qabajeh, L.K.; Qabajeh, M.M. (2010)
Wireless Ad-Hoc networks are collections of nodes that communicate without any fixed infrastructure. A critical problem in Ad-Hoc networks is finding an efficient and correct route between a source and a destination. The need for scalable and efficient protocols, along with the recent availability of small, inexpensive low-power positioning instruments justify adopting position-based routing protocols in mobile Ad-Hoc networks. This paper presents an overview of the existing Ad-Hoc routing protocols that make forwarding decisions based on the geographical position of a packet's destination. We also outline the main problems for this class of routing protocols. We conclude our findings by discussing opportunities for future research.